Regulation of Air Transport The Slumbering Sentinels - Abeyratne, Ruwantissa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Every ten years ICAO holds a worldwide air transport conference. The most recent such event - the 6th Worldwide Air Transport Conference (ATConf/6) - was held in Montreal from 18 to 22 March 2013. The questions posed by this book are: are the (3z(Bclerical and administrative tasks(3y (Bfor ICAO which were decided on by ATConf/6 (and other preceding conferences) sufficient to meet the needs of the people of the world for safe, regular, economical and efficient air transport? Should ICAO not think outside of its 67-year-old box and become a beacon to air transport regulators? In other words, shouldn$1 (Bt the bottom line of ICAO$1 (Bs meaning and purpose in the field of air transport be to analyze trends and guide the air transport industry instead of continuing to merely act as a forum for global practitioners to gather and update information on their respective countries$1 (Bpolicies for air transport? Shouldn$1 (Bt ICAO provide direction, as do other agencies of the United Nations? This book addresses ICAO$1 (Bs inability, unlike most other specialized agencies in their missions, to make a tangible difference in air transport development, through a discussion of key issues affecting the air transport industry. It also inquires into the future of air transport regulation.s
The Nature and Role of ICAO -- Competition in Air Transport -- Connectivity -- The Facilitation Connection -- Consumer Rights -- Airlines - The Other Side of the Coin -- The Black Swan Effect -- Outcome of the Sixth Air Transport Conference (ATConf/6) -- Conclusion.
Keywords: Law; Astronautics; Law; Law of the Sea, Air and Outer Space; Aerospace Technology and Astronautics; Production/Logistics/Supply Chain Management